Anthropometry and functional movement patterns in elite male volleyball players of different competitive levels - Toselli, S.; Campa, F. (The Journal of Strength and Conditioning Research, 2018)
The aim of this study was to establish specific profiles for anthropometry and functional movement parameters and identify which characteristics can be modified by training to achieve a better quality of movement in elite male volleyball players competing at the Italian National League (Super Lega = 39, aged 25.6 ± 4.7 years and A2 = 30, aged 26.2 ± 5.3 years). Another aim was to value functional movement patterns in relation to morphological traits, with special focus on differences by division and playing positions. Statistical significance was set at p = 0.05. According to discriminant analysis, the differences between players of the 2 Divisions were primarily due to nonmodifiable parameters (humerus width, height, and bicrestiliac width) and modifiable parameters (contracted arm circumference and muscle area of upper arm). Our results highlighted differences according to playing positions. Middle hitters and opposites were taller, heavier and generally showed wide dimensions in contracted arm circumference, upper limb length widths, and handgrip strength than the players of the other roles. Percentage of fat mass was low in players of all roles, such as endomorph somatotype component. Ectomorphic component was maximal in middle hitters, whereas mesomorphic component was maximal in liberos. The players of the 2 Divisions did not show differences in the movement patterns, even if approximately 33% of them showed a dysfunctional movement, with a prevalence of asymmetric movements in the shoulder mobility test. Multiple regression showed that, in volleyball players, an optimal flexibility and mobility was closely related to anthropometric characters with particular emphasis on body fat.